2022
DOI: 10.3390/jcm11237168
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Galectin-3 in Patients with Cardiogenic Shock Complicating Acute Myocardial Infarction Treated with Mild Hypothermia: A Biomarker Sub-Study of the SHOCK-COOL Trial

Abstract: Background: Galectin-3 (Gal-3) is considered a potential cardiovascular inflammatory marker that may provide additional risk stratification for patients with acute heart failure. It is unknown whether mild therapeutic hypothermia (MTH) impacts Gal-3 levels. Therefore, this biomarker study aimed to investigate the effect of MTH on Gal-3. Methods: In the randomized SHOCK-COOL trial, 40 patients with cardiogenic shock (CS) complicating acute myocardial infraction (AMI) were randomly assigned to the MTH (33 °C) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Patients with lower serum Gal-3 concentration on the first day after admission demonstrated a higher risk of all-cause mortality at 30 days. Serum Gal-3 concentration on day 1 had a good predictive value for 30-day all-cause mortality with an area under the receiver operating characteristic curve of 0.696 (95% CI: 0.513−0.879), with an optimal cutoff point of less than 3.65 ng/mL [75].…”
Section: Predictor Of Prognosismentioning
confidence: 97%
“…Patients with lower serum Gal-3 concentration on the first day after admission demonstrated a higher risk of all-cause mortality at 30 days. Serum Gal-3 concentration on day 1 had a good predictive value for 30-day all-cause mortality with an area under the receiver operating characteristic curve of 0.696 (95% CI: 0.513−0.879), with an optimal cutoff point of less than 3.65 ng/mL [75].…”
Section: Predictor Of Prognosismentioning
confidence: 97%
“…Особого внимания заслуживает выявленная нами статистически значимая положительная корреляционная связь содержания галектина-3 в плазме крови с возрастом в группе контроля (r s = 0,51, p < 0,05). Основываясь на данных отечественной и зарубежной литературы, можно предположить следующее: эта взаимосвязь обусловлена тем, что галектин-3 рассматривают как профибротическую молекулу, потенциальный маркер фиброза миокарда и печени [7,11,21], а с возрастом многократно возрастает риск развития хронической сердечной недостаточности и сердечно-сосудистых заболеваний. Тем не менее в группе больных РЖ корреляционной взаимосвязи исследуемых маркеров с возрастом мы не обнаружили.…”
Section: участие авторовunclassified
“…In a similar fashion, a review performed on pediatric studies that enrolled patients diagnosed with heart failure concluded that none of the currently available serum biomarkers of myocardial fibrosis perform as well as NT-proBNP in predicting ventricular dysfunction [ 64 ]. Gal-3 was afterwards regarded by the randomized SHOCK-COOL trial as a stable biomarker that correlates well with a 30-day mortality of different causes in patients with AHF and which is not influenced by age, sex and body mass index [ 65 ]. It is therefore unsurprising that Gal-3 has been proposed as a diagnostic biomarker and potential therapeutic target in AHF [ 66 ].…”
Section: Gal-3 Heart Failure and Its Associated Complicationsmentioning
confidence: 99%